SWATH-MS based quantitative proteomics analysis reveals novel proteins involved in PAMP triggered immunity against potato late blight pathogen Phytophthora infestans - Mu, Yang; Guo, Xiao; Yu, Jian; Wang, Ruxun; Liu, Zeng; Hu, Kefan; Song, Jingyi; Chen, Lin; Song, Botao; Du, Juan (Frontiers in Plant Science, 2022)
Potato is the most important non-grain food in the world, while late blight caused by Phytophthora infestans seriously threatens the production of potato. Since pathogen-associated molecular patterns (PAMPs) are relatively conserved, PAMP-triggered immunity (PTI) can provide durable resistance to late blight for potato. However, knowledge of the regulatory mechanisms of PTI against oomycete pathogens at protein levels remains limited due to the small number of identified proteins. In the present work, changes in the proteome profile of Nicotiana benthamiana leaves upon P. infestans PAMP induction were examined using the SWATH-MS (sequential windowed acquisition of all theoretical mass spectra) approach, which provides quantification of protein abundances and large-scale identification of PTI-related proteins. A total of 4401 proteins have been identified, of which 1429 proteins were differentially expressed at least at one time point of 8, 12, 24 and 48 h after PAMP induction, compared with the expression at 0 h when immediately after PAMP induction. They were further analyzed by expression clustering and gene ontology (GO) enrichment analysis. Through functional verification, six novel DEPs of 19 candidates were proved to be involved in PTI responses, including mitochondrial phosphate carrier protein (MPT) 3, vesicle-associated membrane protein (VAMP) 714, lysophospholipase (LysoPL) 2, ascorbate peroxidase (APX) 1, heat shock 70 kDa protein (HSP) 2 and peptidyl-prolyl cis-trans isomerase FKBP (FKBP) 15-1. Taken together, the time course approach and the resulting large-scale proteomic analyses have enlarged our understanding of PTI mechanisms and provided a valuable resource for the discovery of complex protein networks involved in the resistance response of potato to late blight.